EVALUATION OF EARLY AND MID-TERM OUTCOMES OF LAPAROSCOPIC RIGHT HEMICOLECTOMY WITH LYMPH NODE DISSECTION IN ELDERLY PATIENTS - Duy Đạt, Đỗ; Lê Bảo, Hồ; Văn Hưng, Nguyễn (Journal of Health and Aging, 2026)
To evaluate the safety and mid-term outcomes of laparoscopic right hemicolectomy in elderly patients (≥65 years old). A retrospective descriptive study was conducted on 52 patients aged ≥65 years who underwent laparoscopic radical right hemicolectomy with lymph node dissection at Thong Nhat Hospital from 01/2020 to 01/2025. Data analysis was performed using SPSS software version 25.0. The early complication rate was 15.4%, and the 30-day mortality rate was 1.9%. The median number of harvested lymph nodes was 13.2 (92.3% of patients had ≥12 nodes). The 36-month disease-free survival (DFS) and overall survival (OS) rates were 62.5% and 68.9%, respectively. Only 55.6% of indicated patients completed the adjuvant chemotherapy regimen. Laparoscopic right hemicolectomy is a safe, feasible, and oncologically sound procedure for elderly patients. The mid-term survival outcomes were impacted by a low adjuvant chemotherapy completion rate.